Sistem Informasi Pengelolaan Sumber Daya Manusia dengan System Development Life Cycle (SDLC) - Vulandari, Retno Tri (Postulat : Jurnal Inovasi Pendidikan Matematika, 2023)
Human resources (HR) are the only resources that have feelings, desires, skills, knowledge, encouragement, power, and work. All of these potential human resources affect the organization's efforts in achieving its goals. Advances in technology, development of information, availability of capital and adequate materials. Therefore, an HR information system is needed, in this study an information system was developed which has a function to archive data for lecturers, employees, identity archive data, education archive data, and training archive data. The purpose of developing this system is to make it easier for HR staff to manage HR archive data so that they can speed up data processing and produce information. The method used is the system development life cycle (SDLC), which has stages of planning, analysis, design, implementation of trials, and management. The programming language used is PHP and the database system uses MySQL. The results can display information about lecturer data, employee data, identity archive data, education archive data, training archive data, activity archive data and can be printed in the form of a recap in the form of a report.